Heat transfer of 3D-printed porous structure used in cold plate - Tew, Hong Boon (2016)
This project experimentally investigated the heat transfer enhancement capability of 3D-printed porous structures in the application of single-phase forced convection using water and under constant heat flux. The first part of the project involved the design and fabrication of porous structures using Selective Laser Melting. Several porous designs were developed using Computer Aided Design software. However, some of these newly-designed porous structures were not fabricated due to time constraint and unexpected errors. A software-generated porous structure, namely the Rhombi_Octa-Dense, was successfully fabricated for experimental studies. The experimental investigation was carried out using the setup that was built during the span of the project. The reliability of the setup was validated by comparing the experimental results of the bare tube cold plate against numerical simulation performed using “COMSOL Multiphysics” software. Subsequently, experiments were conducted on three porous-filled cold plates with unit cell dimensions of 7 mm, 10 mm and 13 mm, which correspond to porosity values of 64.8%, 75.8% and 95.5%, respectively. The experiments were conducted in a closed circulation loop with ReD ranging from 794 to 4796, with11 data points taken for each cold plate specimen. The results suggest that with the same LD to LL ratio, the porous-filled cold plate of 64.8% has consistently better thermal performances as compared to the other cold plates for the range of flow rates tested. In addition, the results also show that at the highest ReD, the best-performing cold plate has approximately 6 times higher Nu as compared to that of the bare cold plate. Moreover, the investigation also demonstrated that for the same magnitude of thermal enhancement, the 3D-printed porous-filled cold plates have higher porosity as compared to those investigated by Boomsma et al. [1] who employed compressed open-cell foam inserted into the flow channel. The present investigation suggested that the 3D printed porous-filled cold plates eliminate thermal contact resistance along the insert and flow channel interface and thereby enhance heat transfer. Lastly, the investigation shows that the porous-filled cold plates have better thermal performances as compared to the cold plate filled with a typical swirling insert.